2019
DOI: 10.1155/2019/2721357
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel NF1 Frameshift Variant in a Chinese Family with Neurofibromatosis Type 1

Abstract: Neurofibromatosis type 1 (NF1) is a progressive neurocutaneous disorder in humans, mainly characterized by café-au-lait macules (CALMs) and neurofibromas. NF1 is caused by variants of the neurofibromin 1 gene (NF1), which encodes a Ras-GTPase-activating protein called neurofibromin. NF1 variants may result in loss of neurofibromin function and elevation of cell proliferation and tumor formation. In this study, a Chinese NF1 family with an autosomal dominant inheritance pattern was recruited. Exome sequencing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A PN is a severe subtype of NF1 and can involve the eyelid, orbital, periorbital and facial structures [termed orbital-periorbital PN (OPPN)]. Less than 10% of NF1 cases develop PN [38] . Most OPPNs are distributed along the trigeminal nerve, and the most notable sign is blepharoptosis, which occurs in almost all cases, while congenital ptosis associated with NF1 has an incidence rate up to approximately 1% [39] and is usually unilateral.…”
Section: Resultsmentioning
confidence: 99%
“…A PN is a severe subtype of NF1 and can involve the eyelid, orbital, periorbital and facial structures [termed orbital-periorbital PN (OPPN)]. Less than 10% of NF1 cases develop PN [38] . Most OPPNs are distributed along the trigeminal nerve, and the most notable sign is blepharoptosis, which occurs in almost all cases, while congenital ptosis associated with NF1 has an incidence rate up to approximately 1% [39] and is usually unilateral.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that splice site mutations are associated with the tendency to develop neoplasms consisting mostly of central nervous system gliomas and MPNSTs [39]. In the study of Xu et al, the frame shift mutation was detected in all three affected patients in a Chinese family [40]. Corsello et al reported the rate of nonsense mutations, splice mutations and missing mutations as 80% in their study [15].…”
Section: Discussionmentioning
confidence: 95%
“…The gene is difficult to be analysed because it is large and next-generation sequencing (NGS) seems promising to help the genetic diagnostic by covering the Ras-related signalling elements (66,67). Novel variants of NF1 gene such as p.(Gln181Profs*20) have been recently reported (68). Aggressive breast cancer in females with neurofibromatosis type 1 involves germline mutations of neurofibromin 1 in association with other somatic mutations of TP53 or KMT2c (69).…”
Section: Discussionmentioning
confidence: 99%